The Hollywood motion picture blacklist seventy-five years later - Ceplair, Larry 1943- (The University Press of Kentucky, 2022)
"Seventy-five years ago, the Hollywood blacklist ruined lives, stifled creativity, and sent waves of proscription and censorship throughout United States culture. When the Hollywood Ten refused to answer the questions of the House Committee on Un-American Activities about their membership in the Communist Party, they were sentenced to prison, the five who were under contract were fired by their studios, and all were blacklisted from reemployment until they "purged themselves of their communist taint." By the 1950s, this blacklist publicly stigmatized nearly three hundred other Americans in the entertainment industry who invoked the First and Fifth Amendments in their refusal to apologize for their Communist ties or provide the names of other members. Dozens of others were graylisted, as the result of rumors. The Hollywood Motion Picture Blacklist: Seventy-Five Years Later offers new insights on the origins of the blacklist, the characteristics of those blacklisted, and the probability of future proscriptions of the blacklist type. Author Larry Ceplair draws on previously published work while introducing new material to vigorously recount the events that took place between the US government, Hollywood unions, and motion picture studios. Ceplair thoroughly examines the role of Jewish identity in many anti-communist efforts-a concept that has never been fully examined by scholars-and analyzes the actions of subpoenaed witnesses who were forced to choose between cooperating with the House Committee or joining the blacklist. This fascinating book is an illuminating examination of a dark period in American history and the fragility of our rights to free speech and due process. The book includes a comprehensive annotated bibliography and filmography"--
Keywords: USA -- Committee on Un-American Activities; Geschichte; Schwarze Liste; Film; MacCarthyismus; Zensur; USA; United States / Congress / House / Committee on Un-American Activities; Motion picture industry / Political aspects / United States / History / 20th century; Blacklisting of entertainers / United States / History; Blacklisting of authors / United States / History; Motion picture actors and actresses / Political activity / United States; Screenwriters / Political activity / United States; Motion picture producers and directors / Political activity / United States; Communism and motion pictures / United States; Anti-communist movements / United States / History / 20th century; Anti-communist movements; Blacklisting of authors; Blacklisting of entertainers; Communism and motion pictures; Motion picture actors and actresses / Political activity; Motion picture industry / Political aspects; Motion picture producers and directors / Political activity; United States; 1900-1999; History